2015
DOI: 10.1038/ijo.2015.144
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene THSD7A is associated with obesity

Abstract: Body mass index (BMI) is a non-invasive measurement of obesity. It is commonly used for assessing adiposity and obesity-related risk prediction. Genetic differences between ethnic groups are important factors, which contribute to the variation in phenotypic effects. India inhabited by the first out-of-Africa human population and the contemporary Indian populations are admixture of two ancestral populations; ancestral north Indians (ANI) and ancestral south Indians (ASI). Although ANI are related to Europeans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A locus on chromosome 7 with the lead SNP rs78495856 ( p = 4.9 × 10 −7 ) is in an intron of the THSD7A gene. A previous genome-wide association study of BMI found an association with THSD7A ( 25 ).…”
Section: Resultsmentioning
confidence: 88%
“…A locus on chromosome 7 with the lead SNP rs78495856 ( p = 4.9 × 10 −7 ) is in an intron of the THSD7A gene. A previous genome-wide association study of BMI found an association with THSD7A ( 25 ).…”
Section: Resultsmentioning
confidence: 88%
“…rs12154393711,210,9313.8280.7623.06E-060.12740.30926.86E-06 NDUFA4 Candidate gene for role in cellular aging in dental follicle stem cells [57]. THSD7A Obesity candidate gene [58]. rs6947348726,383,7484.6150.7991.70E-070.38090.4373.35E-06 MIR148 Involved in dental stem cells [59].…”
Section: Resultsmentioning
confidence: 99%
“…The locus chr16:28719857 ( p -value 4.36 × 10 − 6 ) contains genes associated with body fat percentage ( APOBR ) [67] and BMI ( SH2B1 ) [68], and rs12154393 (p-value 3.06 × 10–6) contains THSD7A , a candidate gene for obesity [58].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have linked several single nucleotide polymorphisms (SNPs) in WWOX with obesity [21], [22] and T2D [23], [24]. To systematically study the role of WWOX in MetS, we reanalyzed GWAS datasets (n = 27) from the Type 2 Diabetes Knowledge Portal website (www.type2diabetesgenetics.org).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, many GWAS studies have reported several genetic variants in WWOX as among the most significant SNPs and variants associated with obesity and T2D [22], [24]. However, a direct role of WWOX involvement in metabolic disorders is unclear.…”
Section: Discussionmentioning
confidence: 99%